Internationalizing the higher education in Malaysia: Memorandum of Understanding (MoU) - Kayadibi, Saim (Bilsam Yayıncılık, 2011)
It is an unavoidable fact that Higher Education and teachings must upgrade themselves from being local to international. Every era has its own sine qua: if any institution is not updating and renewing itself according to the requirements and needs of the era, it would lag behind of the time and would just repeat and consume the old knowledge rather than invent and innovate. Success is an art of thinking and knowing one step ahead of the time. Not to be left behind of the current time, exchange of information in a mutual ground is necessary. Although there are many ways to implement this fact, the internationally known process of the memorandum of understanding (MoU) might significantly contribute for that purpose. In this research, the developments of MoU relationship of the University of Malaya with other institutions will be explored: looking at the distribution of MoU relationship by year, country based relationships and its durations; regional and geographical patterns; most productive years and active countries also be analyzed. The impact factor which persuaded the researcher to involve in this research is that of the academic visit that was made by three delegates as representatives of the University of Malaya to Turkey in October 2009. Therefore, this paper is aimed to explore the MoU trends of the University of Malaya with other institutions especially the visit made to Istanbul University which may help to contribute some insights for the betterment of the Higher Education System in the World especially in Turkey.